Implementasi Kurikulum Merdeka Pada Mata Pelajaran Bahasa Indonesia Kelas IV di SD Negeri Mengkowo - Retna Iwan Asnawi; Agus Salim Chamidi (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
ABSTRACT The aims of this study were: (1) To find out how the Independent Curriculum is planned for B. Indonesian Class IV subjects at SD N Mengkowo in the 2022/223 academic year, (2) To find out how the Independent Curriculum is implemented for B. Indonesian Class IV subjects in SD N Mengkowo for the 2022/223 Academic Year, and to find out the Evaluation of the Independent Curriculum in Class IV Indonesian Subject B. at SD N Mengkowo for the 2022/223 Academic Year. This study uses a qualitative approach with descriptive analysis methods. The data in this study were obtained from observation, interviews and documentation. The analysis used is qualitative. The technique used is data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1) the implementation of the Independent Curriculum in Indonesian Language Subjects has been implemented at SDN Mengkowo. (2) In planning an independent curriculum there are several things to pay attention to, observing learning outcomes, formulating learning objectives, compiling learning objectives flow, and designing learning. (3) The learning implementation includes several things, such as opening activities, core activities, and closing activities.